CO-PRODUCTION SEBAGAI METODE PENCEGAHAN KEJAHATAN PENCUCIAN UANG DALAM INDUSTRI PERFILMAN HOLLYWOOD: STUDI KASUS RED GRANITE PICTURES TAHUN 2013-2017 - Yulius Tyas Christrianto Kaseger; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2019)
Money laundering has targeted pop culture, and one of which is the film industry. The money laundering case by Red Granite Pictures is the first money laundering case in the film industry. Specific methods are needed to prevent money laundering crimes in the film industry for the better future. The main purpose of this thesis is to analyze co-production cooperation as a method of preventing money laundering, by describing the situation and conditions of the United States and European film industry, the development of co-production cooperation, treatment of the Red Granite Pictures case, and of FATF’s recommendations regarding crime of money laundering . This thesis uses qualitative research methods with explanatory research types and is analyzed by collecting data obtained from books, annual evaluation reports along with recommendations from FATF, also mass media. The explanation of the co-production convention as a method of preventing money laundering using public policy theory, while the national film commission will be analyzed using the theory of neoliberal institutionalism using FATF as the bridging institution. The results of this study indicate that the co-production convention is the suitable policy in preventing money laundering crimes in the film industry. This can be seen from the arrangement of co-production conventions by the European Union, which are in line with the FATF recommendations regarding money laundering.